MOPT reform: A analysis for opportunities of improvement - Loría, Luis Guillermo (2014)
This article aims to bring inescapable aspects, from the point of view of LanammeUCR, should be incorporated in a practical way to the MOPT reform initiative that could be raised. Historically, different entities have referred to the need to reform the MOPT-CONAVI. Based on this, we can identify core issues to consider, as some of them are ultimately key elements to achieve a comprehensive reform, including: exercise MOPT rectory, the system approach and the role of actors, capacity planning, asset management and mainly technical management MOPT-CONAVI. The main aspects that LanammeUCR identified through the exercise of its law’s functions, are opportunities for improvement for MOPT-CONAVI and are considered complementary to achieve a consistent reform with established functions of a the lead agency.